Bronchial varices in a child with tricuspid atresia six years post Fontan correction. Issue 7 (16th July 2020) - Bhushan, Shreya; Goyal, Vikas; Ward, Cameron; Rashid, Muddassir; Kapur, Nitin
Abstract: Tracheal and bronchial varices are rarely found in children. However, they have been described in adults with failing Fontan circuits or secondary to vascular pathology, such as portal and pulmonary hypertension. We report the presentation of haemoptysis and bronchial varices in a child, six years after a Fontan procedure for tricuspid atresia. She had tortuous mediastinal and transpleural arterial collaterals on computed tomography (CT) angiography and cardiac catheterization and subsequently underwent embolization of these collaterals. While the haemoptysis settled post embolization, the bronchial varices persisted on repeat bronchoscopy. She has since been clinically well with no further haemoptysis. Abstract : Tracheal and bronchial varices are rare, especially in children. We report the first presentation of bronchial varices and haemoptysis in a child, six years after a Fontan procedure for tricuspid atresia. She had tortuous mediastinal and transpleural arterial collaterals on imaging and subsequently underwent embolization of these collaterals with haemoptysis settling after this.